Legal Protection of the Sakai Indigenous Community’s Customary Land Rights in the Dispute with PT. Murini Wood Indah Industry - Erlina; Selvi Harvia Santri; Ika Padila (Proceeding International Conference on Social Sciences, 2026)
This study examines the legal protection of the customary land rights of the Sakai indigenous community in the context of a dispute with PT. Murini Wood Indah Industri. Customary rights are the collective rights of indigenous peoples to a specific area that are passed down through generations and have profound social, cultural, and economic significance. However, in practice, the legal recognition and protection of these rights are often unbalanced, particularly when they clash with corporate interests and large-scale development. This dispute case reflects an agrarian conflict influenced by the imbalance of power between indigenous communities and business entities. The study uses a normative-empirical legal method to understand law not only as written norms (law on books) but also as applied social reality (law in action). The results indicate several factors causing the dispute. First, the company cultivated customary land outside the HGU without permits or formal partnerships. Second, the indecisiveness of law enforcement officials and the courts in enforcing legally binding decisions has delayed dispute resolution. Third, the weak recognition and protection of indigenous peoples' rights in the field, despite being normatively guaranteed in the 1945 Constitution, the Basic Agrarian Law, and related sectoral regulations. Overall, legal protection for the customary rights of the Sakai community remains weak, both in terms of formal recognition and dispute resolution mechanisms. This dispute demonstrates the suboptimal implementation of the principle of social justice in natural resource management and the low bargaining position of indigenous communities within the national legal system. Therefore, regulatory strengthening, explicit legal recognition of customary land, and dispute resolution mechanisms that are fair, transparent, and in favor of human rights and local wisdom are needed. This research is expected to contribute to more responsive policies for the protection of indigenous peoples' rights.